Determination of trace thiophanate-methyl and its metabolite carbendazim with teratogenic risk in red bell pepper (Capsicumannuum L.) by surface-enhanced Raman imaging technique - Li, Jiang-Lin; Sun, Da-Wen; Pu, Hongbin; Jayas, Digvir S. (Food chemistry, 2017)
•Trace fungicide TM and its metabolite on red bell pepper surface were detected by SERS imaging.•The optimized LS-SVM model was obtained for predicting TM and its metabolite value.•Uneven residual results were visualized in the TM and its metabolite distribution map.•A novel approach with great potential for analyzing trace jungicide was provided. Surface-enhanced Raman scattering (SERS) imaging coupling with multivariate analysis in spectral region of 200 to 1800cm−1 was developed to quantify and visualize thiophanate-methyl (TM) and its metabolite carbendazim residues in red bell pepper (Capsicum annuum L.). Least squares support vector machines (LS-SVM) and support vector machines (SVM) models based on seven optimized characteristic peaks that showed SERS effects of TM and its metabolite carbendazim residues were employed to establish prediction models. SERS spectra with first derivative (1st) and second derivative (2nd) method were subsequently compared and the optimized model of 1st-LS-SVM acquired showed the best performance (RPD=6.08, R2P=0.986 and RMSEP=0.473). The results demonstrated that SERS imaging with multivariate analysis had the potential for rapid determination and visualization of the trace TM and its metabolite carbendazim residues in complex food matrices.